2020
DOI: 10.1101/2020.04.26.036582
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lineage-specific diversification in the usage of D-glutamate and D-aspartate in early-branching metazoans

Abstract: D-amino acids are unique and essential signaling molecules in neural, hormonal, and immune systems. However, the presence of D-amino acids and their recruitment in early animals is mostly unknown due to limited information about prebilaterian metazoans. Here, we performed the comparative survey of L-/D-aspartate and L-/D-glutamate in representatives of four phyla of basal Metazoa: cnidarians (Aglantha); placozoans (Trichoplax), sponges (Sycon) and ctenophores (Pleurobrachia, Mnemiopsis, Bolinopsis, and Beroe),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Unique NIT (PF08376) domains (Oulavallickal et al, 2017), containing cyclases, were previously identified in Trichoplax (Moroz et al, 2020) as candidates for nitrite/nitrate sensors, similar to bacteria (Shu et al, 2003;Camargo et al, 2007). Mnemiopsis has one sequence (ML02033a) associated with the same cluster (Figure 5) but with a highly derived NIT-like region and unknown function.…”
Section: Soluble Guanylyl Cyclases As Putative Receptors Of No In Cte...mentioning
confidence: 97%
See 2 more Smart Citations
“…Unique NIT (PF08376) domains (Oulavallickal et al, 2017), containing cyclases, were previously identified in Trichoplax (Moroz et al, 2020) as candidates for nitrite/nitrate sensors, similar to bacteria (Shu et al, 2003;Camargo et al, 2007). Mnemiopsis has one sequence (ML02033a) associated with the same cluster (Figure 5) but with a highly derived NIT-like region and unknown function.…”
Section: Soluble Guanylyl Cyclases As Putative Receptors Of No In Cte...mentioning
confidence: 97%
“…This tree confirms a highly derived nature of NOS in ctenophores, probably reflecting their accelerated evolution and a possible bottleneck in their paleontological history around the Permian extinction (Whelan et al, 2017). The tree also highlights several independent radiation events with duplication and triplication of NOSs in lineages leading to placozoans, cnidarians, and vertebrates [see also (Moroz et al, 2020)]. However, representative species from both Porifera and Ctenophora have only one NOS gene.…”
Section: Nos Phylogeny and Derived Nos In Ctenophoresmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemoattractant/repellents can be signaling molecules from microorganisms or other cell types. Symbiont-host signaling can include changes in nitric oxide gradients (Moroz et al, 2020b) or regional differences in amino acid composition, interconversion of D-and L-forms (Moroz et al, 2020a), the formation of oxygen radicals, which are toxic to bacteria, etc.…”
Section: The Nature Of Bacterial Species and Immunitymentioning
confidence: 99%